Improving 4H-SiC/SiO2 interface properties by depositing ultra-thin Si nitride layer prior to formation of SiO2 and annealing - Wang, X.W.; Bu, H.M.; Laube, B.L.; Caragianis-Broadbridge, C.; Ma, T.P. (Mater. Sci. Forum, 2002)
We report dramatic improvement in electrical properties of 4H-SiC/SiO2 interface by depositing an ultra-thin layer of silicon nitride on 4H-SiC prior to formation of silicon oxide and annealing. AC conductance measurements reveal interface-trap density equal to or below 1 × 1012/cm2- eV at energies near the conduction band edge. XPS spectra confirm the presence of N at the interface and suggest possible bonding between N and C. © (2002) Trans Tech Publications, Switzerland.
1 citations (Crossref) [2023-10-31] Journal Abbreviation: Mater. Sci. Forum
Keywords: 4H-SiC MOS; Angle-resolved; Angle-resolved x-ray; Annealing; Chemical bonds; Conductance measurement; Conduction band edge; Deposition; Gate dielectrics; Interface trap density; Interfaces (materials); MOS devices; Nitride layers; Nitrides; Photoelectron spectroscopy; Photoelectron spectroscopy (ARXPS); Si-CMOS; SiC/siO2-interfaces; Silica; Silicon carbide; Silicon nitride; Silicon oxides; Ultrathin films; Ultrathin layers; X ray photoelectron spectroscopy; dept.phy

Thin film thickness and grain structure determination of ferroelectric SrBi2Ta2O9 with cross-sectional atomic force microscopy - Pechkis, Daniel L.; Caragianis-Broadbridge, Christine; Lehman, Ann Hein; Klein, Kate; Han, Jin-ping; Ma, Tso-Ping (Microscopy and Microanalysis, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00148 tex.type: [object Object]
Keywords: dept.phy